Pentingnya Penerapan Literasi Digital dalam Meningkatkan Kreativitas Peserta Didik di Sekolah Dasar - Haya, Aqilla Fadia; Kurniawati, Kurniawati; Hardiyanti, Nadila; Saputri, Irma Armelia (TSAQOFAH, 2023)
The emergence of digital literacy today is due to the development of information and communication technology which is not only printed, but already in digital form. Digital literacy is a form of skill that refers not only to the abillty to use technology, information and communication tools, but also social skills, learning skills, attitudes, critical thinking, creativity and inspiration such as digital skills. Digital literacy can help someone think critically, solve problems and communicate fluently. In addition, digital literacy can provide opportunities to work with people. Digital literacy encourages students to be creative or participate in learning activities freely, creatively and innovatively.